2015
DOI: 10.4317/jced.51770
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to the provision of preventive care among dentists of Udaipur, India

Abstract: Aim: To investigate the practice-, patient- and dentist related barriers to the provision of preventive dental care as perceived by dentists of Udaipur city, Rajasthan, India. Settings and Design:- A cross sectional descriptive survey was conducted among 120 dentists of Udaipur city, Rajasthan. Material and Methods: Mean Content Validity Ratio (CVR) was calculated as 0.87 based on the opinions expressed by a panel of total six academicians. Cronbach’s coefficient was found to be 0.88, which showed a high int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…20 In another study by Nagarajappa et al, patient-related barriers (poor knowledge, unwillingness to pay, ignorance for regular dental visits, poor oral health) were the strongest obstacles for Indian dentists. 17 Similar observation was reported by Rosing et al, 10 Ghasemi et al 21 and Tseng et al 22 In a study Libyan dentists have rated poor knowledge of patients of the potential of caries prevention with the highest score among patient-related barrier. No signi cant difference was observed for the rating of barriers for age, sex and years of practice.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…20 In another study by Nagarajappa et al, patient-related barriers (poor knowledge, unwillingness to pay, ignorance for regular dental visits, poor oral health) were the strongest obstacles for Indian dentists. 17 Similar observation was reported by Rosing et al, 10 Ghasemi et al 21 and Tseng et al 22 In a study Libyan dentists have rated poor knowledge of patients of the potential of caries prevention with the highest score among patient-related barrier. No signi cant difference was observed for the rating of barriers for age, sex and years of practice.…”
Section: Discussionsupporting
confidence: 74%
“…Nagarajappa et al have stated that Indian dentists judged themselves as being the least responsible and patients being most accountable for limited preventive care practice. 17 In the present study among patient-related barriers poor knowledge, unwillingness to pay for preventive care and ignorance for regular dental visits were rated high by practicing dental professionals. Poor oral health was not considered an impediment by the dentists.…”
Section: Discussionmentioning
confidence: 57%
“…However, the scientific literature is not consensual about gender differences on attitudes on prevention and treatment of dental caries. Some researchers have found a more-conservative approach towards prevention and treatment of dental caries among female dentists [23][24][25][26] . In contrast, other studies have found no statistically significant relationship between dentist gender and choices for caries prevention or treatment [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…A closed ended self-administered, study proforma consisting of informed consent, demographics details and questionnaire was distributed to each participant with the allotted time of 35-40 minutes to fill and return. The items for the questionnaire were adapted from 4 sources -theory, observation, expert opinion and previous researches [1,7,8,12]. Before the main survey, the questionnaire was pretested for the feasibility and reliability in 20 dental practitioners.…”
Section: Methodsmentioning
confidence: 99%